Detection of Campylobacter species in stool specimens from patients with symptoms of acute flaccid paralysis in South Africa - Mandile Samantha Thobela; Anthony Marius Smith; Shelina Moonsamy; Heleen du Plessis; Nevashan Govender; Karen Helena Keddy (Journal of Infection in Developing Countries)
Introduction: Guillain-Barré Syndrome (GBS) is an autoimmune disease characterized by acute or subacute symmetrical ascending motor weakness, areflexia, and mild-to-moderate sensory abnormalities. Campylobacter jejuni is reported to be the most common bacterium associated with GBS cases. Despite the eradication of polio, the number of reported GBS cases remains considerably high in South Africa with the causative agents not being well described. Methodology: The aim of the study was to investigate the proportion of Campylobacter spp. detected in stool specimens from patients with symptoms of acute flaccid paralysis (AFP). Stool specimens from patients presenting with AFP, that were negative for polio and non-polio enteroviruses (NPENT), were processed and screened for the presence of Campylobacter spp. using quantitative PCR (qPCR). Results: Of the 512 stool specimens screened between October 2014 to December 2015, 12% (62/512) were positive for Campylobacter spp. Of these 62 Campylobacter infections: 77.4% (48/62) was C. jejuni; 19.4% (12/62) was Campylobacter coli; 3.2% (2/62) was mixed infections of C. jejuni and C. coli. Conclusions: True association of the disease with Campylobacter spp. will enable the proportion of Campylobacter-induced GBS to be better described in South Africa; this can only be done through systematic studies that include bacterial culture and serology together with molecular methodologies.